Monolayer V2O5/TiO2-ZrO2 catalysts for selective oxidation of o-xylene: preparation and characterization - Rao, Komateedi N.; Venkataswamy, Perala; Bharali, Pankaj; Ha, Heon Phil; Reddy, Benjaram M. (SPRINGER, 2012)
A series of TiO2-ZrO2 supported V2O5 catalysts with vanadia loadings ranging from 4 to 12 wt% were synthesized by a wet impregnation technique and subjected to various thermal treatments at temperatures ranging from 773 to 1,073 K to understand the dispersion and thermal stability of the catalysts. The prepared catalysts were characterized by X-ray powder diffraction (XRD), BET surface area, oxygen uptake, and X-ray photoelectron spectroscopy (XPS) techniques. XRD results of 773 K calcined samples conferred an amorphous nature of the mixed oxide support and a highly dispersed form of vanadium oxide. Oxygen uptake measurements supported the formation of a monolayer of vanadium oxide over the thermally stable TiO2-ZrO2 support. The O 1s, Ti 2p, Zr 3d, and V 2p core level photoelectron peaks of TiO2-ZrO2 and V2O5/TiO2-ZrO2 catalysts are sensitive to the calcination temperature. No significant changes in the oxidation states of Ti4+ and Zr4+ were noted with increasing thermal treatments. Vanadium oxide stabilized as V4+ at lower temperatures, and the presence of V5+ is observed at 1,073 K. The synthesized catalysts were evaluated for selective oxidation of o-xylene under normal atmospheric pressure in the temperature range of 600-708 K. The TiO2-ZrO2 support exhibits very less conversion of o-xylene, while 12 wt% V2O5 loaded sample exhibited a good conversion and a high product selectivity towards the desired product, phthalic anhydride.
Keywords: VANADIUM-OXIDE CATALYSTS; PHTHALIC-ANHYDRIDE; STRUCTURAL-CHARACTERIZATION; TIO2-ZRO2 CATALYSTS; TITANIA CATALYSTS; UTILIZING CO2; SOFT OXIDANT; DEHYDROGENATION; OXIDEHYDROGENATION; ETHYLBENZENE